The Development And Significance Of Business Intelligence (BI) Platforms In Facilitating The Decision-Making Process In Dubai Government Entities - ALMHEIRI, ABDULLA OBAID MOHAMMED (2022)
Business Intelligence (BI) technologies provide a flexible platform for businesses to properly store, process, analyse and report data and processes. The use of BI technologies in handling critical data and facilitating data-driven decision making (DDD) has been realised by many literature studies. However, its application and benefits for the Dubai government entities for effective data management and decision making have not been investigated before. Thus, the current study has focused on analysing the significance of BI platforms in improving the decision-making process in the Dubai Statistics Center (DSC), a governmental entity in Dubai. Using secondary research design, the study determined factors that impact the decision-making process in Dubai government entities. Furthermore, the significance of using the BI platform for decision-making is established in the light of academic and empirical evidence. A BI platform using ArcGIS software is also developed demonstrating the visual and realistic application of interactive data in decision-making regarding different aspects of DSC such as population, marriages, education, etc. The recommendations are provided retarding the effective use of BI platforms in DSC and other government entities in Dubai. The current study will contribute to knowledge and practice to promote the use of BI platforms in making effective decisions. Future work includes integration with Artificial Intelligence (AI) for the AI-based BI platforms which would allow the translation of theoretical solutions into actionable tasks.